Technoculture and the digital technological mediation of social interactions in the Cybersociety: Írida García de Molero; Aminor Méndez; Olaya Rangel - García de Molero, Írida; Méndez, Aminor; Rangel, Olaya (Quórum Académico, 2024)
This research studies technoculture as a set of cultural practices associated with social discourse mediated by digital communication technologies, which operate in the culture of the Cybersociety. The research is qualitative, documentary (Martínez Miguélez, 2004) and sociosemiotic with an interpretative-analytical textual approach (Verón, 1996). By applying Verón’s theory of social discursiveness, we reached an analytical understanding of the processes of production of the meaning of technological digital genres, in whose texts the communicative relations in the personal and professional life of users are reconfigured.